Effect of bedrock stiffness and thickness on numerical simulation of seismic site response. Italian case studies. Issue 139 (December 2020) - Falcone, Gaetano; Romagnoli, Gino; Naso, Giuseppe; Mori, Federico; Peronace, Edoardo; Moscatelli, Massimiliano
Abstract: Evaluation of bedrock stiffness and thickness effect on ground motion modification represent a key-issue in the perspective of seismic risk reduction policy, since the maximum depth of site prospection generally does not extend down to the stiff bedrock location. Site conditions were identified from the Italian database of seismic microzonation studies. Simplified and realistic numerical models were adopted, i.e. extended down to the soft and stiff bedrock, respectively, in order to perform seismic site response analyses. Results indicate that simplified numerical model provides a quantification of the surface ground motion modification with an error generally equal to ±10% with respect to the realistic model. Hence, the evaluation of seismic performance of sites based on simplified numerical models represents a support tool for seismic risk management at large area. Highlights: Numerical models of national site conditions were identified from Italian database. Simplified numerical models were extended down to the soft geological bedrock. Realistic numerical models were extended down to the stiff seismic bedrock. Simplified numerical models can support seismic risk management and urban planning. Impedance contrast between shallow bedrock layers affect the numerical input motion.